Rotational Paper-Based Microfluidic-Chip Device for Multiplexed and Simultaneous Fluorescence Detection of Phenolic Pollutants Based on a Molecular-Imprinting Technique - Qi, Ji; Li, Bowei; Wang, Xiaoyan; Fu, Longwen; Luo, Liqiang; Chen, Lingxin (Analytical chemistry (Washington), 2018)
In this study, we first present rotational paper-based microfluidic chips (RPADs) combined with a molecular-imprinting (MIP) technique to detect phenolic pollutants. The proposed rotational paper-based microfluidic chips could implement qualitative and quantitative analysis of two different phenolic contaminants, 4-nitrophenol (4-NP) and 2,4,6-trinitrophenol (TNP), simultaneously. Qualitative and quantitative analysis could be implemented simultaneously through fluorescence-intensity changes depending on the structures of quantum dots combined with a molecular-imprinting technique. Moreover, the rotational paper-based microfluidic chips provide a low cost, flexible, and easy way to operate the entire process conveniently. Under the optimal conditions, the proposed sensors showed high sensitivity and selectivity. Our final experimental results illustrated that the detection limits of 4-NP and TNP in the paper-based quantum-dot MIP (PQ-MIP) RPADs ranged from 0.5 to 20.0 mg/L, with detection limits of 0.097 and 0.071 mg/L, respectively. This novel rotational paper-based microfluidic device shows great potential and versatility for multiplexed, portable, and rapid testing of environmental and biological samples in the future.